Metode Zero Suffix Dalam Meminimumkan Biaya Pengiriman Barang (Studi Kasus PT. Aspac Cargo) - Ega Rizka Wahyuni; Arnellis Arnellis (UNIVERSITAS NEGERI PADANG, 2021)
Logistics business activities, expedition services and couriers are sectors that experienced a growth spurt and even showed an increase in transaction value. PT. Asia Pacific Dirgantara (Aspac Cargo) is an expedition service company that requires a mechanism in the distribution of goods. In the distribution of goods, planning to determine shipping costs is very influential. Good planning makes PT. Aspac Cargo is superior to other shipping companies so that it can get maximum profit. The purpose of this study was to determine the minimum cost of shipping goods at PT. Aspac Cargo using the Zero Suffix method and the minimum cost percentage obtained by PT. Aspac Cargo in minimizing the cost of shipping goods using the Zero Suffix method. This research is applied research and the data used are data on delivery of goods, data on demand for delivery of goods and data on the cost of shipping goods from the city of origin to the city of destination. The final result of the application of the Zero Suffix method to minimize the cost of shipping goods at PT. Aspac Cargo is Rp. 322,322,000 and the percentage of the minimum cost obtained by PT. Aspac Cargo in minimizing the cost of shipping goods using the Zero Suffix method, which is 16.9%